When Tinder Swiping Gets Challenging: Women’s Narratives of Gender-Based Violence as Shared Through Quora - Sabili, Zivana; Poerwandari, Elizabeth Kristi (UI Scholars Hub, 2023)
Amidst the popular use of Tinder in urban society, the decision whether or not to date someone tends to be made quickly based on a photo and a short profile description. Simple as it may seem, there are moments when swiping gets challenging, especially for women. Tinder has a notorious reputation when it comes to gender-based violence. Unfortunately, despite the significant increase in online dating apps usage during the COVID-19 pandemic, this phenomenon is still highly underresearched. In this qualitative netnographic research, we explore Tinder sexual harassment narratives uploaded by women in Quora. Through judgment sampling, 15 answers from 7 questions posted by Quora users and 12 comments were analyzed. Criteria of inclusion for answers are as follows: Answers should (1) contain personal account on violence and/or harassment related to Tinder-use, (2) be written by women, (3) indicate that the perpetrator is male. Data were analyzed through thematic analysis. Four main themes emerged: the forms of gender-based violence experienced by women while dating men from Tinder, women’s feelings after experiencing gender-based violence perpetrated by their Tinder dates, women’s responses after experiencing gender-based violence from their Tinder dates, and responses from other Quora users after reading women’s stories on gender-based violence experienced through Tinder.